Adaptive Market Hypothesis: Evidence from Sharia Stocks in Asian countries - Djauhari, Haikal; Rahmawati, Rahmawati; Al Arif, Muhammad Nur Rianto (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: The adaptive market hypothesis, which is a new way to test capital market performance that reconciles the efficient market hypothesis (EMH) with behavioral finance, is the focus of our research. Our study's novelty lies in testing the efficiency of the Islamic capital market in six Asian countries: Bangladesh, India, Indonesia, Malaysia, Pakistan, and Thailand, over different periods: before, during, and after the COVID-19 pandemic.Research Objectives: We aim to delve into its application in the Islamic capital market, which has seen significant growth in recent years.Research Methods: We employed the variance ratio test, the ARIMA model, and the Elman neural network to test efficiency.Empirical Result: Our findings revealed that the efficiency of sharia indices in these countries was not constant over the three periods, thereby supporting the existence of the adaptive market hypothesis.Implications: The results of this study are not only important for academic discourse but also offer practical applications for investors to refine their investment strategies, engaging the audience in a discussion on Islamic capital market efficiency.JEL Classification: G02, G14, G15